1990
DOI: 10.1007/bf01310506
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phorbol ester-induced neutrophil chemiluminescence by FeLV

Abstract: Receptor-mediated activation is accompanied by phospholipid metabolism and by calcium fluctuation resulting in a chemiluminescence (CL) response in the neutrophil. This pathway involves activation of protein kinase C (PKC) and the NADPH oxidase. Artificial stimulants such as phorbol esters, specifically 12-O-tetradecanylphorbol-13-acetate (TPA), circumvent the receptor-mediated pathway and activate PKC resulting in a measurable CL response. Neutrophils from feline leukemia virus (FeLV) exposed cats were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that FeLV infection affects neutrophil function and their response to different stimuli (Kiehl et al, 1987;Dezzutti et al, 1989Dezzutti et al, , 1990Hoffmann-Jagielska et al, 2005). Thus, neutrophils from FeLV + experimentally infected and clinically ill cats show a reduced chemotactic response in vitro in comparison with neutrophils from FeLV 2 cats (Kiehl et al, 1987).…”
Section: Neutrophil Phagocytosismentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that FeLV infection affects neutrophil function and their response to different stimuli (Kiehl et al, 1987;Dezzutti et al, 1989Dezzutti et al, , 1990Hoffmann-Jagielska et al, 2005). Thus, neutrophils from FeLV + experimentally infected and clinically ill cats show a reduced chemotactic response in vitro in comparison with neutrophils from FeLV 2 cats (Kiehl et al, 1987).…”
Section: Neutrophil Phagocytosismentioning
confidence: 99%
“…Thus, exogenous H 2 O 2 generated from NADPH oxidase induced NET release in mammals and release of heterophil extracellular traps in chickens (Fuchs et al, 2007;Chuammitri et al, 2009). FeLV infection inhibits neutrophil activation by inhibition of protein kinase C and a decrease in ROS production Lewis et al, 1986;Lafrado et al, 1987;Dezzutti et al, 1989Dezzutti et al, , 1990Hoffmann-Jagielska et al, 2005).…”
Section: Characterization Of Feline Netsmentioning
confidence: 99%
See 1 more Smart Citation